Addressing health needs of the homeless in Delhi: Standardising on the issues of Street Medicine practice. Issue 11 (2nd November 2022) - Coleman, Harry Laurence Selby; Levy-Philipp, Liam; Balt, Elias; Zuiderent-Jerak, Teun; Mander, Harsh; Bunders, Joske; Syurina, Elena
ABSTRACT: Due to barriers in accessing and using healthcare services, a large proportion of the care homeless populations receive comes from informal providers. In Delhi, one such informal programme, called Street Medicine, provides healthcare outreach to homeless communities. Clinical practice guidelines are set to be developed for Street Medicine teams in India and form the object of this research. This study uses a social-ecological model to understand the barriers facing Street Medicine teams and the homeless as they attempt to address the latter's healthcare needs; coupling it with an analytical approach which situates these barriers as the issues within practice through which standardisation can take place. A qualitative inquiry, comprising three months of observations of Street Medicine outreach and interviews with over 30 key informants, was conducted between April and July 2018. The analysis identified novel barriers to addressing the needs of homeless individuals, which bely a deficit between the design of health and social care systems and the agency homeless individuals possess within this system to influence their health outcomes. These barriers – which include user-dependent technological inscriptions, collaborating with untargeted providers and the distinct health needs of homeless individuals – are the entry points for standardising, or opening up, Street Medicine practices .